Influence of Intellectual/Emotional/Spiritual Intelligence, Independence, and Tri Hita Karana on Auditor Performance - Putri, I Gusti Ayu Made Asri Dwija; Wirawati, Ni Gusti Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020)DO - 10.24843/JIAB.2020.v15.i01.p08, 2020)
Auditor performance is the result of work rendered in carrying out one’s duties within a certain period of time. The quality of auditing is improved if the auditor shows good performance. The aim of this research is to determine how intellectual/emotional/spiritual intelligence, independence, and the culture of Tri Hita Karana affect auditor performance in public accounting firms in Bali. This research was conducted in seven public accountant firms in Bali and questionnaires were used to collect the data. Purposive sampling was employed to determine the sample, and multiple linear regression was applied as a technique of analysis. This research contributes to the literature as it considers Tri Hita Karana as a factor that affects auditor performance. Hopefully, this research can give guidance to public accounting firms in terms of how intellectual/emotional/spiritual intelligence, independence, and Tri Hita Karana influence auditor performance. Keywords : Tri Hita Karana , auditor, intelligence, independence